Efektivitas Mindfulness-Based Interventions Terhadap Penerimaan Diri Pada Pasien Hemodialisis di Rumah Sakit Pendidikan Prof. Dr. Chairuddin Panusunan Lubis Universitas Sumatera Utara - Pasaribu, Indah Septiani; Tanjung, Dudut; Siregar, Farida Linda Sari (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Patients on hemodialysis have several mental and physical difficulties. Improved self-acceptance is necessary since psychological problems can have a substantial impact on patient’s quality of life, ranging from stress to depression. The purpose of this study is to assess how well mindfulness-based interventions (MBIs) can help hemodialysis patients feel more accepting of themselves. Using a pretest–posttest control-group design and a quasi-experimental methodology, the study included 68 patients receiving regular hemodialysis at RSP Prof. Dr. Chairuddin P. Lubis USU. The subjects were split into two groups, each with 34 patients: the intervention group and the control group. The MBI intervention chosen by the author is Mindfulness-Based Cognitive Therapy (MBCT). With an average score of 102 ± 14.98, the results demonstrated a substantial rise in self-acceptance scores in the intervention group. On the other moment, the control group's average score of 109.56 ± 6.25 did not indicate any improvement. Following the intervention, there was a significant difference in the intervention and control groups' self-acceptance scores, as indicated by a Mann-Whitney test (p=0.040). According to the research, MBIs help hemodialysis patients feel more confident in themselves. Future studies can build on this work to provide more thorough and successful therapies aimed at enhancing hemodialysis patients' sense of self-acceptance. Keywords: Hemodialysis, Mindfulness, Mbis, MBCT, Self-Acceptance  ABSTRAK Pasien hemodialisis memiliki banyak masalah fisik dan psikis, masalah psikis yang muncul bisa berupa stress hingga depresi yang dapat memengaruhi kualitas hidup pasien, sehingga dibutuhkan peningkatan penerimaan diri. Salah satu pendekatan yang ingin diuji adalah pendekatan Mindfulness-Based Interventions (MBIs) terhadap peningkatan penerimaan diri. Tujuan penelitian ini adalah untuk mengetahui efektivitas MBIs terhadap penerimaan diri pasien hemodialisis. Metode penelitian menggunakan quasi experimental dengan metode pretest–posttest control-group design, sebanyak 68 orang pasien yang menjalani hemodialisis regular di RSP Prof. Dr. Chairuddin P Lubis USU. Subjek penelitian dibagi menjadi dua kelompok yaitu kelompok intervensi dan kelompok kontrol dengan masing-masing kelompok berjumlah 34 orang. Penulis memilih Mindfulness-Based Cognitive Therapy (MBCT) sebagai intervensi MBIs. Hasil penelitian menunjukkan nilai skor penerimaan diri pada kelompok intervensi mengalami peningkatan signifikan dengan rerata 102 ± 14,98. Pada kelompok kontrol tidak memperlihatkan peningkatan dengan rerata 109,56 ± 6,25. Uji Mann whitney memperlihatkan perbedaan nilai skor penerimaan diri yang signifikan antara kelompok intervensi dan kelompok kontrol sesudah pemberian intervensi (p=0,040).  Berdasarkan hasil penelitian dapat ditarik kesimpulan MBIs efektif terhadap peningkatan penerimaan diri pada pasien hemodialisis. Diharapkan penelitian ini menjadi dasar bagi peneliti berikutnya untuk merancang intervensi yang lebih komprehensif dan efektif dalam peningkatan penerimaan diri pasien hemodialisis. Kata Kunci: Hemodialisis, Mindfulness, Mbis, MBCT, Penerimaan Diri